Availability of Occupational Safety and Health (OSH) Facilities and Potential Hazards in a Senior High School Biology Laboratory: A Compliance Assessment Against Indonesian National Standards - Hidayah Dwi Cahyati; Rosita Astiani Silmi; Adzkia Jannatun Hanis; Aulia Niken Sari; Evi Muliyah (BIOCHEPHY: Journal of Science Education, 2026)
The biology laboratory plays an important role in science learning through practical work. However, laboratory activities also have potential hazards that can threaten user safety if occupational safety and health (K3) facilities are not optimal. This study aims to identify the availability of K3 facilities, potential hazards, and compliance with the standards of Permendikbud No. 8 of 2018 in the Biology Laboratory of SMAN X Tangerang Selatan. A descriptive method with a mixed approach (qualitative and quantitative) was used. Data were collected through observation using a checklist (40 items), interviews with laboratory assistants, and documentation. The results showed the level of availability of K3 facilities was 55% (complete category). Hazard identification found that chemical hazards were the main potential (10% of the total items), especially from corrosive and flammable materials. Facilities such as eyewash stations, evacuation routes, and B3 waste bins were not yet available. This study concluded that the laboratory generally met basic safety standards, but needed improvement in emergency response facilities and waste management.